2017
DOI: 10.1186/s12948-017-0070-7
|View full text |Cite
|
Sign up to set email alerts
|

Preventive actions of allergen immunotherapy: the facts and the effects in search of evidence

Abstract: Allergen immunotherapy (AIT) is the only treatment that works on the causes of allergy. Available AIT nowadays are subcutaneous immunotherapy (SCIT) and sublingual immunotherapy (SLIT) for allergic rhinitis and asthma, while for allergy to Hymenoptera venom only subcutaneous route is recommended. A bulk of trials and meta-analyses demonstrated that efficacy and safety of AIT in decreasing allergic clinical symptoms and use of rescue medications, while its preventive capacity is yet under investigation. The mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 51 publications
1
14
0
Order By: Relevance
“…11,12,13 Most of them confirmed a large profile of the safety of rapid protocols, especially when the initial therapy lasted a maximum of 48 hours. 5,13 Data have also shown that the ultrarush protocol is the safest, 14,15 and our results confirm this finding. More adverse reactions have been observed in patients with an allergy to bee venom.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…11,12,13 Most of them confirmed a large profile of the safety of rapid protocols, especially when the initial therapy lasted a maximum of 48 hours. 5,13 Data have also shown that the ultrarush protocol is the safest, 14,15 and our results confirm this finding. More adverse reactions have been observed in patients with an allergy to bee venom.…”
Section: Discussionsupporting
confidence: 86%
“…The protection with VIT achieved up to a 90-95% level of success. 1,5 The VIT to wasp or bee venom were used different allergen products due to completely different antigen sequences of this venom and the absence of significant cross reactivity and cross allergy between the wasp and bee venoms. 1 The adverse reactions during VIT were observed as local or systemic reactions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, both ARC symptoms and symptomatic medication use were significantly reduced, by 22%‐30% ( P < 0.005 for all 5 years) and 27% vs placebo ( P < 0.001), respectively . Similarly, the Preventive Allergy Treatment (PAT) study showed that a 3‐year course of SCIT with standardized allergen extracts (birch and grass pollen) in children resulted in long‐term clinical effects, with a significantly lower asthma incidence among SCIT‐treated patients (relative to symptomatic medication alone) observed at 7 years after treatment cessation . Finally, the prior analyses of the LRx database provide real‐world evidence of the long‐term benefits of grass pollen SLIT in patients with AR with or without associated asthma in terms of slower progression of AR and AA medication intake, and reduced risk of new‐onset asthma medication use …”
Section: Discussionmentioning
confidence: 95%
“…There are many studies on immunotherapy and AD; however, outcomes of the reports are conflicting, and contrary to studies on allergic rhinitis, efficacy is questionable in AD [169]. Atopic march, a severe problem in children with AD, should be prevented; however, the preventive role of allergen immunotherapy has not been demonstrated yet [170]. Nevertheless, patients with severe AD and accompanying allergic rhinitis and/or asthma may be considered for allergen immunotherapy [171].…”
Section: Allergen Immunotherapymentioning
confidence: 99%